2014–2016 seasonal rainfall effects on metals in tea (Camelia sinensis (L.) Kuntze). (March 2019) - Huang, Hui; Kfoury, Nicole; Orians, Colin M.; Griffin, Timothy; Ahmed, Selena; Cash, Sean B.; Stepp, John Richard; Xue, Dayuan; Long, Chunlin; Robbat, Albert
Abstract: Plant-climate interactions affect the edible crop composition, impacting flavor, nutrition, and overall consumer liking. In this study, principal components analysis was used to assess the macro- and micronutrient metal concentrations in pre-monsoon (spring), monsoon (summer), and post-monsoon (autumn) tea ( Camelia sinensis (L.) Kuntze) from Yunnan Province, China in 2014–2016. Statistical differences were observed (p = 1.35E-24). Fe, Ca, Mg, Mn, Al, and Ba concentrations were higher in June (monsoon) than in March (pre-monsoon) and September (post-monsoon) compared to Pb, K, Cu, Zn, and Na, which were higher in March and September. Although Fe, Ca, Mg, Mn, Al, and Ba concentrations increased during the monsoon season, sensory analysis did not detect metallic taste in either minimally processed or farmer-processed (commercial) teas. This finding shows the seasonal differences in flavor were due to striking differences in organic chemical composition and concentration. Highlights: Metal nutrient concentrations in tea varied in response to climate changes. Concentrations of Fe, Ca, Mg, Mn, Al and Ba were higher in monsoon tea. Concentrations of Pb, K, Cu, Zn, and Na were higher in pre- and post-monsoon tea. Sensory analysis revealed no metallic taste in environmental and commercial teas.